Generic prescribing: A cross-sectional study comparing the prescribing practices of a HSE and a NHS hospital - Murphy, James; McWilliams, Sebastian; Kennedy, Julia (Trinity Student Medical Journal, 2010)
Background: Generic prescribing is currently a politically important topic in Ireland as it is seen as a potential source for easing the healthcare budget. Objective: To compare prescribing practices at a Health Service Executive (HSE) and a National Health Service (NHS) hospital, with an emphasis on the level of generic prescribing. Design: A comparative cross-sectional study. Data Source: Bedside drug charts and medical notes of surgical and medical inpatients. Methods: Each ward in the respective hospitals was sampled once between July 2009 and September 2009; all patients (over age 17 years) present were included as subjects at the time of assessment. Patient demographics, in addi- tion to the name, dose, frequency, and route of administration of prescribed drugs, were recorded. Clinical pharmacist (CP) review was also noted. A da- tabase was constructed for statistical analysis. Results: HSE hospital patients (n=301) and NHS hospital patients (n=296) re- ceived 3640 drug prescriptions (52.5% generic) and 3962 prescriptions (79.7% generic), respectively. A lower level of CP chart monitoring was noted in the HSE hospital (41.5% versus 97%, p<0.001). The rate of drug chart errors was 4.2% in the HSE and 1.5% in the NHS hospital. For all proton pump inhibitors (PPIs) prescribed in the HSE hospital, generic substitution could have saved €23.83/day, according to the Monthly Index of Medical Specialities (MIMS). Conclusion: Increased generic prescribing in the HSE hospital has potential cost and safety benefits.